Argument-based negotiation among BDI agents - Rueda, Sonia Vivian (2002)
Negotiation is a basic mechanism for interaction that allows the members in a Multiagent System to coordinate their actions and to reach a favorable agreement. When agents are collaborative, the negotiation process progresses through a dialogue in which proposals and counter-proposals are exchanged in a common effort to advance towards a mutual agreement. An Interaction Protocol regulates communication and gives structure to the dialog. Most interaction protocols designed to regulate negotiation among agents are abstract models based in some real world negotiation practice (e.g. auctions). Here we propose a deliberative mechanism for negotiation among BDI agents based in Argumentation.